ความสัมพันธ์ของระบบนิเวศชุมชนลุ่มแม่น้ำเลยกับการเปลี่ยนแปลง, The Relationship between Ecological Community on Loei River Basin and Changes - บัวระภา, อำภา (Asian Creative Architecture, Art and Design, 2018)
Abstract Rivers and watersheds, changing seasonally, are important areas of Loei Province. In Wang Saphung district, during rainy season this district and adjacent areas are seasonally inundated by high level of floodwater, but there is very low water level in winter. Human settlement is located close to the Loei River. People have adapted the land use in relation to season changes, including rainy, summer, and winter, for instance, fishing, vegetable planting, animal farming, bathing, cloth washing, and resting. These various activities associated with natural changes creating the Loei River community’s eco system. In the past, both the nature and community looked after the watershed. However, the changes in the socio-economic system make the community change its way of life. Factors including expansion of farmland and waterfront cultivation made farmers accelerate framing growth by using chemicals, and community’s disposal of wastewater from homes and shops without treatment deteriorate the ecosystems. Some parts of the river are seriously dry during the drought, then solving the problem by dredging. Thus, the ecosystem has been deteriorated. The watershed fish and indigenous plants have been disappeared. The community has abandoned the lifestyle that once bound and rely on the river. Community identity is fading. The purposed solutions are consciousness stimulation and law enforcement along with design, such as the construction of a stepped dam, a natural weir, tree plantation for reducing soil erosion, wastewater treatment using plants and the design of waterfront dam is to support community recreation linking the community and the river in the changing of contexts and lifestyles. Keywords: Watershed Area, Ecological Community, Ecological Culture